THE ROLE OF ENVIRONMENTAL AWARENESS, INNOVATION, AND PRICE IN ENCOURAGING INTEREST IN BUYING ELECTRIC VEHICLES - Hironimus Hari Kurniawan; Agus Purnomo Sidi (Jurnal Apresiasi Ekonomi, 2024)
This study aims to identify and analyze the influence of environmental awareness variables, innovative behavior, and price on electric vehicle (EV) buying interest in Indonesia. Using a quantitative approach, data was collected through an online survey involving 225 respondents from various major cities in Indonesia. The results of the analysis show that environmental awareness (X1) and price (X3) have a significant positive correlation with the buying interest of electric vehicles, with Spearman correlation values of 0.696 and 0.766, respectively. This indicates that the higher the environmental awareness and positive perception of the price of electric vehicles, the greater the interest of consumers to buy electric vehicles. In contrast, innovative behavior (X2) showed a weaker correlation with buying interest, with a correlation value of 0.375, indicating that technological innovation, while valued, is not a dominant factor in the purchase decision of electric vehicles. The coefficient of determination (R²) of 0.604 reveals that 60.4% of the variation in electric vehicle buying interest can be explained by these three variables, while the remaining 39.6% may be influenced by other factors such as product quality and infrastructure availability. These findings provide insights for electric vehicle manufacturers and policymakers to prioritize environmental and price awareness factors in their marketing strategies to drive wider adoption of electric vehicles in Indonesia.